A Reference Genome Assembly of American Bison, Bison bison bison. (17th February 2021) - Oppenheimer, Jonas; Rosen, Benjamin D; Heaton, Michael P; Vander Ley, Brian L; Shafer, Wade R; Schuetze, Fred T; Stroud, Brad; Kuehn, Larry A; McClure, Jennifer C; Barfield, Jennifer P; Blackburn, Harvey D; Kalbfleisch, Theodore S; et al.
Abstract: Bison are an icon of the American West and an ecologically, commercially, and culturally important species. Despite numbering in the hundreds of thousands today, conservation concerns remain for the species, including the impact on genetic diversity of a severe bottleneck around the turn of the 20th century and genetic introgression from domestic cattle. Genetic diversity and admixture are best evaluated at genome-wide scale, for which a high-quality reference is necessary. Here, we use trio binning of long reads from a bison–Simmental cattle ( Bos taurus taurus ) male F1 hybrid to sequence and assemble the genome of the American plains bison ( Bison bison bison ). The male haplotype genome is chromosome-scale, with a total length of 2.65 Gb across 775 scaffolds (839 contigs) and a scaffold N50 of 87.8 Mb. Our bison genome is 13× more contiguous overall and 3400× more contiguous at the contig level than the current bison reference genome. The bison genome sequence presented here (ARS-UCSC_bison1.0) will enable new research into the evolutionary history of this iconic megafauna species and provide a new tool for the management of bison populations in federal and commercial herds.